Penerapan Platform E-Commerce Acehsale terhadap UMKM di Aceh - Fachrina, Maulida; Putri Salsabilla, Fazira; Syifa Asyura, Cut (Program Studi Ilmu Administrasi Negara Bekerjasama dengan Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This study aims to critically analyze the contextualization of e-commerce adoption and the digital strategy utilized by Micro, Small, and Medium-sized Enterprises (MSMEs) in Aceh within the contemporary digital ecosystem. A qualitative research approach was employed, structuring the analysis around a four-dimensional framework: digitization, transformation, engagement, and contextualization. The study examined digitization efforts to integrate MSMEs onto digital platforms (e.g., AcehSale), transformation concerning the leveraging of e-commerce to expand market reach and sales; engagement as the strategic customer interaction necessary for fostering loyalty and contextualization, emphasizing the incorporation of Aceh's unique local and cultural context into the digital business model. The findings indicate that while significant progress has been made in digitization and market transformation, MSMEs continue to face considerable structural barriers. Primary challenges identified include low digital literacy, intense market competition, and inadequate internet infrastructure. Consequently, the study concludes that sustained and inclusive growth requires strategic governmental intervention focusing on targeted digital literacy education, effective engagement strategy development, and improved accessibility to essential resources to cultivate a resilient digital economy in Aceh.